Auditors' Report and Financial Statements: For the year ended 31 December 2006 - S. F. Ahmed & Co., Chartered Accountants (S. F. Ahmed & Co., Chartered Accountants, 2013)
Auditors' Report and Financial Statements for the period from 31st December 2005 to 31st December 2006